Mild manifestation of methanol poisoning half a day after massive ingestion of a fuel alcohol product containing 70% ethanol and 30% methanol: a case report. Issue 3 (10th April 2018) - Yoshizawa, Tomohiro; Kamijo, Yoshito; Fujita, Yuji; Suzuki, Yoshiki; Hanazawa, Tomoki; Usui, Kiyotaka; Kishino, Tohru
Abstract : Case: Is fomepizole necessary after massive ingestion of a mixture of methanol and ethanol? We report the case of a 37‐year‐old man who was transported to our Poison Center 12 h after ingesting 500 mL of fuel alcohol containing 70% methanol and 30% ethanol in a suicide attempt. On admission, he presented only with somnolence and mild metabolic acidosis. We hypothesized that most of the ethanol had been metabolized. Outcome: As the estimated serum concentration of methanol was lethal (242.6 mg/dL), fomepizole was given i.v. and hemodialysis was carried out twice, resulting in complete recovery. Later, the serum concentrations of both methanol and ethanol on admission were found to be 224.1 and 0.51 mg/dL, respectively. Conclusion: Therapeutic intervention was delayed by half a day after ingestion of a product containing methanol and ethanol in the present case. If the patient had arrived earlier, he may have only been treated with hemodialysis, but not fomepizole. Abstract : A 37‐year‐old man was transported to our Poison Center 12 h after ingesting 500 mL of fuel alcohol containing 70% methanol and 30% ethanol, presenting only with somnolence and mild metabolic acidosis. He was successfully treated with fomepizole and hemodialysis. Later, the serum concentration of methanol on admission was found to be lethal (224.1 mg/dL), but the amount of ethanol was small (0.51 mg/dL). We concluded that the patient may have only been treated with hemodialysis, but not fomepizole, if he had arrived earlier.